Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2000
DOI: 10.1046/j.1440-1746.2000.02060.x
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C in injecting drug‐using women during and after pregnancy

Abstract: Pregnancy does not adversely affect the course of hepatitis C. A modest rebound in ALT levels, but not HCV-RNA, occurs after delivery in some viraemic women. This supports the theory that immune mechanisms rather than direct viral cytopathology are involved in hepatocyte injury during HCV infection. Hepatitis C infection did not influence pregnancy complications and outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 15 publications
2
14
0
Order By: Relevance
“…30-32 In one study, viremia in HCV seropositive mothers was associated with PROM. 33 In this study, we also report evidence for a possible association between maternal HCV infection and PROM.…”
Section: Commentssupporting
confidence: 61%
“…30-32 In one study, viremia in HCV seropositive mothers was associated with PROM. 33 In this study, we also report evidence for a possible association between maternal HCV infection and PROM.…”
Section: Commentssupporting
confidence: 61%
“…In one study, viraemia in anti-HCV positive mother was associated with Premature Rupture of Membranes. (33) In present study 11.29% of anti-HCV positive women had pregnancy induced hypertension and antepartum haemorrhage. Our findings are consistent with the findings of Goyal L.D.et al (14) Latt et al also found higher rate of pregnancy induced hypertension among HCV RNA positive women.…”
Section: Discussionsupporting
confidence: 44%
“…Our findings are consistent with the findings of Goyal L.D.et al (14) Latt et al also found higher rate of pregnancy induced hypertension among HCV RNA positive women. (33) .In a study Reddick et al found no association between HCV infection and preeclampsia, but the same study showed that individuals with Hepatitis-B and Hepatitis-C coinfection had increased risk for Antepartum haemorrhage. (30) The present study reports intra uterine fetal deathin 11% anti-HCV positive women.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic hepatitis C is mild in menstruating women [34]; its activity is suppressed during pregnancy and enhanced after delivery [35]. The velocity of fibrosis progression is extremely low in young women exposed to HCV through mass-administration of immunoglobulin-D. Only two of 184 (1.2%) and four of 1,018 (0.4%) developed cirrhosis over 24 years and 20 years, respectively, in Irish and German studies [36,37].…”
Section: Discussionmentioning
confidence: 99%